A puzzle for Logan - MacAndrew, Richard (Cambridge ; New York : Cambridge University Press, 2003)
Edinburgh inspector Jenny Logan must figure out whether the murder of a young woman is connected to convicted killer Ronnie Campbell's escape from prison.
Adult
Adult
Keywords: English language -- Textbooks for foreign speakers; Murder -- Investigation -- Fiction; Police -- Scotland -- Edinburgh -- Fiction; Readers (Adult); Women detectives -- Fiction; Criminal investigation -- Fiction; English as a second language; Homicide -- Fiction; Mystery fiction; Police -- Edinburgh (Scotland) -- Fiction; Reading materials; Women detectives -- Fiction; Edinburgh (Scotland) -- Fiction; Edinburgh (Scotland) -- Fiction; Mystery fiction